2022
DOI: 10.1002/pc.26717
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of polymer micro/nano composites with two‐level mechanical reinforcing procedure

Abstract: Biocompatible composite production was accomplished by utilizing two-level hierarchical approach for mechanical reinforcement. A well-known commodity polymer; low-density polyethylene (LDPE), which has high-fracture toughness, yet low strength and modulus was used as the main matrix material. As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is also known that PVP is highly hydrophilic, and moisture absorption leads to chain breakage; thereby, bulk specimens could not be produced in our previous study. 25 Similarly, for high-thickness coatings, the moisture effect could be more effective in the upper parts of the film.…”
Section: Elastic Modulusmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that PVP is highly hydrophilic, and moisture absorption leads to chain breakage; thereby, bulk specimens could not be produced in our previous study. 25 Similarly, for high-thickness coatings, the moisture effect could be more effective in the upper parts of the film.…”
Section: Elastic Modulusmentioning
confidence: 99%
“…In order to confirm the reliability of PVP elastic modulus, the indentation test was repeated for smaller indentation depths of 200-400 nm for pristine PVP, revealing again the average elastic modulus of 3.9 GPa, details of which are given in our previous study. 50 Therefore, the measured elastic modulus values are trustworthy, and the substrate influence could be excluded. The indentation depth of nanocomposites is approximately 50% lower than the pristine polymer, making the nanocomposite films even less prone to the substrate effect.…”
Section: Elastic Modulusmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the commonly used methods to overcome this drawback is by modifying the properties of epoxy resin by loading them with rigid fillers. [ 1–8 ]…”
Section: Introductionmentioning
confidence: 99%
“…One of the commonly used methods to overcome this drawback is by modifying the properties of epoxy resin by loading them with rigid fillers. [1][2][3][4][5][6][7][8] Previous works [9][10][11][12][13][14][15][16][17] have already shown that the toughening of the epoxy resins with both organic and inorganic nanofillers can substantially influence their characteristics and the selection of the toughener depends on the epoxy properties to be varied.…”
Section: Introductionmentioning
confidence: 99%